2017
DOI: 10.1007/s00417-017-3783-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and morphological outcome in patients with chronic central serous chorioretinopathy treated by subthreshold micropulse laser

Abstract: BackgroundChronic central serous chorioretinopathy is a serious therapeutic problem as it may lead to significant visual impairment. The aim of this retrospective study is to evaluate functional and morphological effects, as well as factors influencing visual outcome in patients treated by subthreshold micropulse laser.MethodsFifty-one eyes with chronic central serous chorioretinopathy lasting longer than 4 months (18 months on average) underwent up to two sessions of subtreshold micropulse laser treatment. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 53 publications
2
22
1
Order By: Relevance
“…This was also reported in a recent study emphasizing younger patients responded better to therapy with 577 nm SMYL. 41 Although our findings suggest that 577 nm SMYL for CCSC is effective and safe, this new laser modality may not completely prevent the recurrence of CCSC with multiple leakage in older patients.…”
Section: Discussioncontrasting
confidence: 58%
“…This was also reported in a recent study emphasizing younger patients responded better to therapy with 577 nm SMYL. 41 Although our findings suggest that 577 nm SMYL for CCSC is effective and safe, this new laser modality may not completely prevent the recurrence of CCSC with multiple leakage in older patients.…”
Section: Discussioncontrasting
confidence: 58%
“…This could again be indicative of the effect of laser in decreasing choroidal hyperpermeability through a mechanism not completely understood. Other studies have also shown that SDM laser decreases recurrences of CSC …”
Section: Discussionmentioning
confidence: 86%
“…Outer nuclear layer thinning at the central fovea should indicate cone photoreceptor loss, considering the distribution of rod and cone photoreceptors. Gawecki et al used SDM laser for treatment of chronic CSC and demonstrated that although the laser provided good morphological results, there was no significant improvement in visual acuity. They concluded that in order to achieve good visual results, SDM laser should be considered in acute cases.…”
mentioning
confidence: 99%
“…A greater visual acuity improvement and CMT reduction were observed during the first months after treatment in most of the studies. 4,14,19,20 For reference, 12 weeks seems to be enough to test the efficacy of this new wavelength in cCSR; this time frame has been used in other studies to understand the response and to weight other treatment options. 2,4,8,9,14,20 In our study, there were no significant changes in BCVA which seem inferior than the other studies that evaluated micropulse laser for cCSR.…”
Section: Discussionmentioning
confidence: 99%